Influence of free surface, unsteadiness and viscous effects on oar blade hydrodynamic loads - Leroyer, A.; Barre, S.; Kobus, J.-M.; Visonneau, M. (Journal of Sports Sciences, 2010)
Flow around a rowing blade is a very complex phenomenon, involving unsteady three-dimensional flow with violent motion of the free surface. However, in the literature, forces acting on blades are modelled using extreme and dubious simplifications. The aim of the present study was to evaluate the influence of free surface and unsteadiness (two physical characteristics that are commonly neglected when modelling loads on blades) as well as viscous effects. In fact, quasi-static approaches are often used, with no influence of the free surface effects. To conduct this study, computational fluid dynamics is used, supported by experimental results performed with a dedicated device reproducing a simplified rowing stroke in the towing tank. Comparisons show that both free surface flow and unsteadiness must be considered to capture the whole physics of the phenomenon accurately. In contrast, the viscous effects have a very limited influence.